Typtonomenaeus formosanus gen. et sp. nov., a new sponge-associated pontoniine shrimp (Crustacea: Decapoda: Palaemonidae: Pontoniinae) from northern Taiwan - Marin, Ivan; Chan, Tin-Yam (Zootaxa, 2013)
A new genus and species of sponge-associated pontoniine shrimps (Crustacea: Decapoda: Palaemonidae: Pontoniinae) is described from northern part of Formosa Island (Taiwan). The new species can be clearly recognized by convex robust nail-like apices on dactyli of both pereiopods II—a unique morphological structure among pontoniine shrimps. Morphological differences from all known sponge-associated pontoniine genera are discussed.